Intercultural Perspectives on DAS RADIKAL BÖSE and THE ACT OF KILLING. Similarities and Dissimilarities in Coping with Trauma in Indonesia and Germany, in Southeast Asia and Europe Intercultural Perspectives on DAS RADIKAL BÖSE and THE ACT OF KILLING - Freek L. Bakker (Journal for Religion, Film and Media, 2018)
This article offers a close reading of DAS RADIKAL BÖSE (RADICAL EVIL, Stefan Ruzowitzky, DE 2013) and THE ACT OF KILLING (Joshua Oppenheimer, ID / USA 2012) - two very different films - that nevertheless provide images of the same topic by focusing different facets of it. These filmic works arise from very different situations and context, referring to historic events in countries lying in a large geographic and chronologic distance from each other. But in these two completely different contexts, also from a religious perspective, something maybe detected which universally human. The thoughts of Zygmunt Bauman and Emmanuel Levinas may be helpful in this exploration of three scenes in which the perpetrators seem to break down when they realise what they did to the women and children.